UNCTAD Handbook of Statistics 2024 - UN Trade; Development (United Nations, 2025)
The UNCTAD Handbook of Statistics was first launched in 1967. Over the past 50 years, the handbook has evolved to incorporate new statistics and ensure that readers have access to the best possible information available. The 2024 edition of the Handbook continues in this tradition of excellence and innovation. As in previous years, this edition showcases 'nowcasted' estimates for total merchandised trade, total services trade and GDP. PDF version is only a snapshot of a comprehensive web version containing more data and themes.